Magnetomotive Displacement of Magnetic Nanoparticles in Different Tissue Phantoms - Huber Christian Marinus; Heim Christian; Li Jiaqi; Ermert Helmut; Rupitsch Stefan J.; Ullmann Ingrid; Lyer Stefan (Current Directions in Biomedical Engineering)
Magnetic nanoparticles (MNPs) can be used in various biomedical applications, such as magnetic drug targeting (MDT) or magnetic hyperthermia for cancer treatment. MNPs are injected into the body and accumulated with an external magnetic field at the tumor site. For therapy monitoring, the MNPs distribution has to be accurately mapped in real time. Magnetomotive ultrasound (MMUS) is a suitable technique for this purpose. It was already demonstrated that MMUS can map the accumulation process of MNPs during MDT. Moreover, inverse MMUS is an advanced technique to quantify MNP distribution. This method simulates the displacement of MNPs and surrounding tissues and compares the results to measured data. Understanding how magnetomotive displacement behaves in various elastic environments is crucial for advancing inverse MMUS and accurately quantifying MNP distributions. In this study, ultrasound tissue phantoms were fabricated with varying elastic parameters, incorporating MNPs. Subsequently, their MMUS displacement is assessed.